Model of Tourist Behavioral Intention through Tourist Emotion and Tourist Involvement - Herawati, Heny; Suldina, Farida (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research aims to analyze the behavior model of tourists in Bali when visiting Health Spas from a positive legal perspective. Traveler behavioral intent is an important factor in measuring the success of a travel company, as it can influence the decision to revisit and recommend destinations to others. The data collection method was carried out through questionnaires, while data analysis was carried out using the Structure Equation Model (SEM) method. The results of the study show that the emotions of tourists positively and significantly affect behavioral intentions. However, the image of tourist destinations cannot be a mediating variable between tourist emotions and behavioral intentions. The image of tourist destinations and perceived value can mediate the relationship between tourist emotions and behavioral intentions. Tourist involvement also has a positive and significant effect on behavioral intentions through the value felt by tourists. This research provides implications that tourist destination managers need to consider emotional factors and perceived value perceived by tourists in their marketing strategies.